Bringing Literature and Linguistics into EFL Classrooms : Insights from Research and Classroom Practice. - Zacharias, Nugrahenny T. (Cambridge Scholars Publishing, 2011)
The articles presented in this book bring together educators' work and experiences from various teaching contexts (Indonesia, Malaysia, Nepal, and Australia) in the teaching English in EFL contexts. This publication, therefore, offers this richness and diversity of contexts and experiences to the readers. What sets this book apart from existing books is its balance between and explicit coverage of both research, theoretical and practical aspects of teaching. This project has been prompted by ...